Intravenous lacosamide in seizure emergencies: Observations from a hospitalized in-patient adult population. (November 2016) - d'Orsi, Giuseppe; Pascarella, Maria Grazia; Martino, Tommaso; Carapelle, Elena; Pacillo, Francesca; Di Claudio, Maria Teresa; Mancini, Daniela; Trivisano, Marina; Avolio, Carlo; Specchio, Luigi M.
Highlights: IV LCM is effective in seizure clusters in a hospital adult setting. IV LCM is effective in established focal status epilepticus. The loading of IV LCM was well tolerated, with mild adverse effects. Abstract: Purpose: to evaluate the efficacy and safety of intravenous (IV) lacosamide (LCM) in the treatment of seizure clusters (SC) and status epilepticus (SE) in hospitalized adult patients. Methods: we prospectively analyzed treatment response, seizure outcome, and adverse effects of IV LCM in 38 patients with seizure emergencies (15 with SC, 23 with SE) during a hospital stay. The loading dose of IV LCM was 200–400 mg and the maintenance dose was 200–400 mg daily. Response to IV LCM was evaluated within 20 min, 4 h and 24 h of LCM infusion. Results: an acute anti-seizure effect after IV LCM was especially evident when it was first used – (SC) or second line (established SE) treatment. In particular, 87% of SC patients (13/15) and 80% of established SE (8/10) demonstrated response to LCM treatment, while no patients with super-refractory SE (0/8) responded to IV LCM according to our criteria. The loading of IV LCM was well tolerated, with mild adverse effects (2/38 temporary dizziness). In most patients, during and after administration of the loading dose of IV LCM a temporary (30 min–1 h) sedation was observed. No ECG and laboratory values-changes were documented in any of the patients. Conclusions: LCM is an effective and well-tolerated treatment when used to treat SC in hospitalized adult patients. As add-on therapy, it may be useful to stop seizure activity in patients with focal SE not responding to first/second-line intravenous AEDs.